CORRELATES OF SELF-REPORTED ARTHRITIS IN ADULT PAKISTANI POPULATION - Shaikh, Irshad Ali; Shaikh, Masood Ali (Journal of Ayub Medical College Abbottabad, 2005)
Osteoarthritis is a common joint disease with high morbidity and adverse economic impact on societies1. The most common risk factors include age and obesity2. To describe, age gender, literacy and residency status associated with self reported arthritis in adults and its prevalence in Pakistan, we used data from the National Health Survey of Pakistan (NHSP) 1990-94; with written permission from the federal Ministry of Health, Islamabad. We selected all the adults aged 26 and above who responded to the question Have you ever had Arthritis? individuals responding affirmatively to this question were identified as having arthritis. A two-stage stratified sample design was adopted for NHSP3. Design-based analysis with SUDAAN 9.01 was done using Logistic regression, Odds Ratios (OR) were computed for the association of arthritis with various demographic variables. The overall prevalence of arthritis 39%, and 95% Confidence Interval (CI) was 34%, 43% (n = 5851). In males arthritis prevalence was 30% 95% CI 25%, 34%, while prevalence in females was 47% CI 41%, 53%. Adults with arthritis were more likely to be in the age group of 41 to 55 years (OR 1.58, 95% CI 1.37, 1.82), and 56 years and above group (OR 1.84, 95% CI 1.60, 2.1) compared to 26-40 year age group. Males were almost half as likely to report arthritis compared to females (OR 0.52, 95% CI 0.40, 0.66). Arthritic adults were more likely to be rural dwellers (OR 1.53, 95% CI 1.12, 2.08) compared to urban dwellers, and compared to literate adults (defined as being able to read and write) adults who were not literate were more likely to report arthritis (OR 1.73, 95% CI 1.41, 2.12). While compared to single adults, married adults were more likely to report arthritis (OR 1.61, 95% CI 1.36, 2.28), no statistically significant association was found between reporting arthritis and being in the other category comprising of divorced, widowed and separated adults. Results of Hosmer-Lemeshow goodness-of-fit tests using Wald F and Chi-Square conclude that the model was a good fit for the data. The results of this unique survey, demonstrate that rural women above the age of 40 years were most likely to report arthritis; health education efforts at early diagnosis and treatment would be particularly beneficial for this group.